Survey of Early Practices and Perceptions of Liver Machine Perfusion Among US Liver Transplant Surgeons - Michelle C. Nguyen, MD, MPH, FACS; Xingjie Li, MD; Chi Zhang, MD; Stephanie Ohara, MD; Mehrdad Motamed, MSIS; Caroline C. Jadlowiec, MD, FACS; Adyr A. Moss, MD; Kunam S. Reddy, MD; Amit K. Mathur, MD, MS, FACS (Transplantation Direct)
Background. Ex vivo machine perfusion (MP) has transformed organ preservation, offering significant benefits in liver transplantation (LT), particularly with high-risk donor grafts. However, adoption in the United States has been limited. We aimed to examine early adoption trends, surgeon perceptions, and barriers to implementing MP in the United States after Food and Drug Administration approval of MP platforms. Methods. A 23-question electronic survey was distributed to members of the American Society of Transplant Surgeons between October and November 2022, capturing attitudes and practices related to MP adoption. Responses from 96 surgeons representing 77 LT centers across 11 Organ Procurement and Transplantation Network regions were analyzed. Results. Forty-four respondents (48%) reported having an MP program at their institution. Adoption of MP was significantly more common in high-volume centers and those performing ≥20 donation after circulatory death (DCD) transplants annually (P < 0.001). MP utilization received strong support, with 88% endorsing its use for DCD liver allografts and 82% for donation after brain death allografts. Respondents cited MP’s ability to reduce ischemic cholangiopathy, enable graft repair, and facilitate viability assessment as key benefits. Normothermic MP was preferred for high-risk donor profiles, including DCD grafts, older donors, and steatotic livers, and was associated with an increased willingness to accept medically complex grafts compared with static cold storage. Barriers to MP utilization included program costs, personnel demands, and logistical complexities. Centers with higher proportions of privately insured patients were more likely to adopt MP. Despite these challenges, 84% of respondents expressed interest in future MP adoption. Conclusions. MP enhances graft utilization and outcomes, particularly for complex and high-risk donor livers, but widespread US adoption requires addressing financial and logistical barriers. Future efforts should focus on refining cost-effectiveness analyses, collaboration with organ procurement organizations and device companies, and developing standardized training to optimize MP integration and maximize its clinical impact on LT.